The Dispute About the Middle Ages: Some Reflections on the Cultural Identity of Europe: J. Le Goff, J. Kloczowski, A. Gurevic - Brzezińska, Anna M. (2018)
The book is a proposal of reading the works of the leading European medievalists of the twentieth century in the cultural context of medievalism, understood here as a belief in the fundamental role of the Middle Ages for the development of a specifically European system of values. An innovative idea was to use a comparative perspective for three historiographic traditions: Polish, French and Russian. Inscribing into the “bright legend” of the Middle Ages through perceiving such values as respecting differences with respect for local tradition, subsidiarity and solidarity towards the community, the three historians indicate the basic features of European unity, actively shaping the debate on the identity of contemporary Europe.
Keywords: Jacques Le Goff; Jerzy Kłoczowski; Aron Guriewicz; medievalism; Polish historiography; historical anthropology; history of ideas